Crystal Structure Analysis and Magneto‐Transport Investigation of Co1−xFexSi (with x = 0% to x = 20%). (17th December 2021) - Schnatmann, Lauritz; Lammel, Michaela; Damm, Christine; Levin, Aleksandr A.; Pérez, Nicolas; Novikov, Sergey; Burkov, Alexander; Reith, Heiko; Nielsch, Kornelius; Schierning, Gabi
Abstract: Cobalt monosilicide, CoSi, belongs to the new class of materials, featuring Weyl nodes in the bulk band structure, located very close to the Fermi energy. By shifting the chemical potential into these Weyl nodes using Fe‐doping, quantum effects like the chiral anomaly and weak anti localization have been evidenced. However, the behavior of these effects with respect to the doping concentration is largely unexplored. Crystal structure and the electrical transport properties in single crystalline CoSi micro‐ribbons with different Fe‐doping are studied to identify the characteristic temperatures of electronic quantum and correlation effects. For the crystal structure analysis, transmission electron microscopy and powder X‐ray diffraction analysis with a refined structural model is performed based on Le Bail fitting to analyze the lattice parameter. Hereby, the change of the lattice parameter of Co1− x Fe x Si is shown with increasing Fe content. In the electrical transport analysis, the occurrence of chiral anomaly and the weak anti localization effect in Fe‐doped CoSi are presented. It is shown that these effect can be tailored by Fe‐doping in CoSi. Abstract : Crystal structure and electrical transport of Co1− x Fe x Si have been investigated. Samples with 0% to 20% Fe have been synthesized and analyzed by electron microscopy and X‐ray diffraction including refinement. The electrical transport has been characterized as temperature and magnetic field dependent and interpreted by a semi‐classical fitting model. Hereby, contributions of chiral anomaly and weak anti‐localization have been be identified.